Analysis of the Effect of Labor Allocation on Changes in Farmer Household Income Due to the Development of the Gasing Industrial Zone in Talang Kelapa District, Banyuasin Regency - Muhammad Arbi (Jurnal Indonesia Sosial Teknologi, 2024)
Banyuasin Regency has experienced rapid industrial growth, including the Gasing Industrial Estate in Gasing Village, Talang Kelapa District. This study analyzes farmer household labor allocation and its effect on total household income due to nearby industrial activities. This research uses the survey method through observation, interviews, and a literature study and is presented descriptively and analytically. The results of this study indicate that the average allocation of farmer household labor in rice farming is 55.45 HOK per hectare per year. Meanwhile, the allocation of labor of farm household members from non-farm activities derived from the existence of activities around the location of the growing industrial area is 213.71 HOK per year. Farmer household income from rice farming by calculating family labor wages is Rp. 4,995,843.48 per hectare per year with an average farmer income of Rp. 10,667,225.12 per hectare per year, while rice farming income that does not account for labor wages is Rp. 3,413,163.98 per hectare per year with an average income of Rp. 11,458,564.87 per hectare per year. Furthermore, from the results of simple linear regression analysis, it is known that the allocation of labor allocation has a significant effect on the total income level of farmer households living around the gasing industrial area in Gasing Village, Talang Kelapa Subdistrict, Banyuasin Regency.